2020
DOI: 10.1186/s12984-020-00739-6
|View full text |Cite
|
Sign up to set email alerts
|

Passive, yet not inactive: robotic exoskeleton walking increases cortical activation dependent on task

Abstract: Background: Experimental designs using surrogate gait-like movements, such as in functional magnetic resonance imaging (MRI), cannot fully capture the cortical activation associated with overground gait. Overground gait in a robotic exoskeleton may be an ideal tool to generate controlled sensorimotor stimulation of gait conditions like 'active' (i.e. user moves with the device) and 'passive' (i.e. user is moved by the device) gait. To truly understand these neural mechanisms, functional near-infrared spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Because the fNIRS recorded raw data contained various noises, fNIRS raw data was pre-processed with the MATLAB TM 17.0 (MathWorks, United States) software by the following procedure to improve the signal-to-noise ratio (SNR) (Supplementary Figure 1). Firstly, noisy channels were rejected if any of the following situations were met: (I) The optical intensity (OI) range exceeded the 0.5-1,000; (II) The source-detector separation range exceeded the range from 0 to 45; and (III) The ratio of the mean and standard deviation of the optical intensity [mean(OI)/std(OI)] is less than 2 (Huppert et al, 2009;Peters et al, 2020). Secondly, for a given subject, if the percentage of the subject's rejected channels over all channels exceeds 50%, the subject with poor signal quality was also rejected, which was in line with the previous fNIRS study (Hakuno et al, 2020).…”
Section: Fnirs Data Pre-processingmentioning
confidence: 99%
“…Because the fNIRS recorded raw data contained various noises, fNIRS raw data was pre-processed with the MATLAB TM 17.0 (MathWorks, United States) software by the following procedure to improve the signal-to-noise ratio (SNR) (Supplementary Figure 1). Firstly, noisy channels were rejected if any of the following situations were met: (I) The optical intensity (OI) range exceeded the 0.5-1,000; (II) The source-detector separation range exceeded the range from 0 to 45; and (III) The ratio of the mean and standard deviation of the optical intensity [mean(OI)/std(OI)] is less than 2 (Huppert et al, 2009;Peters et al, 2020). Secondly, for a given subject, if the percentage of the subject's rejected channels over all channels exceeds 50%, the subject with poor signal quality was also rejected, which was in line with the previous fNIRS study (Hakuno et al, 2020).…”
Section: Fnirs Data Pre-processingmentioning
confidence: 99%
“…Although we did not directly measure muscle effort or participants’ perceptions of effort, we consider it unlikely that they were completely passive, which could explain the lack of difference between these two conditions. A study that compared passive and active modes of robotic gait found that muscle activity in the passive mode was about 50% of that recorded during the active mode [ 45 ]. Similarly to our results, brain activation levels did not differ between the two lowest effort conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, given that functional improvement in post-stroke walking ability is a product of neuromuscular recovery and movement compensations [ 61 ], there may have been differences between groups in the nature of walking improvement that were not captured by our included outcomes. Current research of the impact of robotic-assisted walking on other measures such as brain plasticity, muscle activation symmetry, and kinematic qualities of gait may support alternate reasons for utilizing an exoskeleton in stroke rehabilitation [ 51 , 62 , 63 ]. It is also important to consider the emotional and psychological benefit of standing and practicing walking for patients after stroke.…”
Section: Discussionmentioning
confidence: 99%